Implementation of Serious Image Media In Developing The Cognitive Development Aspects of Early Children - Oktavia, Dewi Mike; Nadya, Junaisih Dewi; Lestari, Puji; Amaliyah, Ekfi Rosyidah; H.K, Itaqillah (Syntax Literate, 2021)
This study aims to prove that there is an effect of using serial image media on cognitive development by playing science activities to recognize butterfly metamorphosis. This study used a quantitative research design, quasi experimental design with a pretest-posttest controlled group design model. Learning in the control group uses a conventional model that is centered on the teacher while in the experimental group using serial image media. This research was conducted in RA. Masyithah 5 Karanganyar Paiton in group B with 20 children for the control group and 20 children for the experimental group as research subjects. From this research, it shows that there is an influence on the experimental class children who use serial image media has a higher average when compared to the control class who uses the conventional model that is centered on the teacher. The average score for the experimental class was 82.25 and the mean score for the control class was 75.5. Based on the data analysis that has been done, that tcount> ttable, namely 2.163> 2.08387. Thus it can be concluded that serial image media has an effect on cognitive development by playing science activities to recognize butterfly metamorphosis.